The Dimensions of Multicultural Education and Character Education in Forming Students Who Think Critically and Tolerantly - Yondrizal; Rismalaini; Julhadi (Walidem Institute and Publishing, 2024)
Objective: This article aims to analyze the dimensions of multicultural education and character education as well as the integrative contribution of both in forming critically thinking and tolerant students. The study focuses on the role of education in responding to the challenges of diversity in multicultural societies. Theoretical framework: The theoretical framework of this research rests on the theory of multicultural education and character education. Multicultural education emphasizes recognition of diversity and social justice, while character education focuses on internalizing moral values. The integration of the two is the basis for the formation of critical thinking and student tolerance. Literature review: The literature shows that multicultural education contributes to the strengthening of attitudes of tolerance, while character education shapes moral values and social behavior. However, studies that integrate both approaches in shaping critical thinking and tolerance are still limited. This is the basis for the development of this study. Methods: This study uses a qualitative approach with a literature study method. Data was obtained from books, national and international journals, and education policy documents. Data analysis is carried out through content analysis to examine and synthesize relevant concepts. Results: The results of the study show that multicultural education fosters students' critical awareness through an understanding of diversity and social justice. Character education reinforces the values of tolerance, empathy, and moral responsibility. The integration of the two forms of holistic learning. Implications: The findings of this study make a theoretical contribution to the development of the study of multicultural and character education. Practically, the results of the research can be a reference for educators in designing learning that fosters critical thinking and student tolerance. Novelty: The novelty of this article lies in the integration of multicultural education and character education in a single conceptual framework. This study places critical thinking and tolerance as simultaneous outcomes of holistic education in the context of a multicultural society.